碳纤维包裹金属氧化物的电容器用柔性电极及制备方法 (2018)
本发明公开种碳纤维包裹金属氧化物的电容器用柔性电极及制备方法，通过对金属氧化物纳米粒子表面修饰等，可利用静电纺丝技术制备碳纳米纤维（维碳材料）腔内包裹金属氧化物纳米粒子柔性膜，用于柔性超级电容电极。不仅柔性好，而且碳纳米纤维可为金属氧化物那纳米粒子工作时的体积变化提供充分的缓冲空间，减小金属氧化物的体积效应，具有比电容高、稳定性好等优点，进步提高了柔性电容的性能。另外，生产过程无需表面化学沉积或电沉积等方法，操作简单、材料结构可控、成本低，适合大批量工业生产。 The invention discloses a flexible electrode with carbon fiber wrapped metal oxide for a capacitor and a preparation method. Through surface modification of metal oxide nanoparticles and the like, a flexible membrane that metal oxide nanoparticles are wrapped with a carbon nano fiber (a one-dimensional carbon material) is prepared by using an electrospinning technique, and the flexible membrane can be used in a flexible super-capacitor electrode. Not only is good flexibility achieved, a sufficient buffer space can be provided for volume variation of the metal oxide nanoparticles in operation through the carbon nano fiber, the volume effect of the metal oxide can be reduced, advantages of high specific capacitance, good stability and the like can be achieved, and the properties of